The efficacy and harm of prostaglandin analogues for IOP reduction in glaucoma patients compared to dorzolamide and brimonidine: a systematic review. Issue 1 (21st December 2007) - Hodge, W G; Lachaine, J; Steffensen, I; Murray, C; Barnes, D; Foerster, V; Ducruet, T; Morrison, A
Abstract : Aim: To systematically review the literature on the efficacy and harm of prostaglandin analogues (PGAs) compared to brimonidine and dorzolamide in treating elevated intraocular pressure (IOP). Methods: Keywords were searched in major literature databases to identify relevant randomised clinical trials (RCTs) of PGAs for ophthalmic use. The study quality of RCTs was assessed using the Jadad scale. Outcomes assessed included reduction in IOP in individual patients, adverse events (AEs) and withdrawals due to AEs. Results: Eight unique RCTs evaluating a total of 1, 722 individuals were included in this systematic review. Analysis did not show a significant reduction in the mean IOP from patients receiving latanoprost compared with those receiving brimonidine (WMD = −1.04; p = 0.30). On the other hand, the latanoprost group showed a significant reduction in mean IOP compared to the dorzolamide group (WMD = −2.64; p<0.00001). The number of ocular AEs (excluding hyperaemia) was significantly higher in the brimonidine group compared with the latanoprost group (RR = 0.66; p = 0.0005). Conclusion: Latanoprost was found to be significantly superior to dorzolamide but not brimonidine. However, ocular adverse events were significantly fewer in latanoprost users than in brimonide users. Neither travoprost nor bimatoprost was compared to dorzolamide or brimonidine in the present literature.